DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) THROUGH COMPANY CHARACTERISTICS AT COMPANY LISTED ON LQ45 INDONESIA STOCK EXCHANGE (IDX) - Budiyono Budiyono; Dewi Maryam (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2017)
In the era of globalization, environmental awareness has brought about changes in attitudes towards profit orientation of the social orientation of the company. Management as the agent cannot avoid the reality of the impact of corporate activity that not only generates profits / raise stock prices, but also has environmental impacts such as damage to ecosystems, pollution, and so forth. The purpose of this study was to analyze the influence of firm characteristics on corporate social responsibility disclosure in corporate annual reports in Indonesia. The populations in this study are 10 companies listed in the LQ45 index of the Indonesia Stock Exchange (IDX) with the research period of 2011 until 2015 and meet the criteria established. Analysis of the Data used is multiple linear regressions. The results of this study indicate that public ownership, liquidity, and firm size have no significant effect on corporate social responsibility disclosure. Meanwhile, leverage and profitability have a significant effect on corporate social responsibility disclosure. Keywords: corporate social responsibility disclosure, public ownership, leverage, liquidity, profitability, and firm size.